2010
DOI: 10.1080/03088839.2010.503713
|View full text |Cite
|
Sign up to set email alerts
|

The exposure of shipping firms’ stock returns to financial risks and oil prices: a global perspective

Abstract: Full terms and conditions of use: http://www.informaworld.com/terms-and-conditions-of-access.pdf This article may be used for research, teaching and private study purposes. Any substantial or systematic reproduction, redistribution , reselling , loan or sub-licensing, systematic supply or distribution in any form to anyone is expressly forbidden. The publisher does not give any warranty express or implied or make any representation that the contents will be complete or accurate or up to date. The accuracy of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 65 publications
0
19
0
Order By: Relevance
“…Evidence on the influence of news in crude oil prices on shipping companies' stock returns is again mixed. On one hand, Grammenos and Arkoulis (2002) reported that companies' stock returns were negatively affected by oil price changes, Kavussanos and Marcoulis (2000), Drobetz et al (2010) and El-Mashry et al (2010) on the other, argued that oil prices may be a contributor to stock returns given that oil is the major input for generating cargo service.…”
Section: Factor Constructionmentioning
confidence: 99%
See 1 more Smart Citation
“…Evidence on the influence of news in crude oil prices on shipping companies' stock returns is again mixed. On one hand, Grammenos and Arkoulis (2002) reported that companies' stock returns were negatively affected by oil price changes, Kavussanos and Marcoulis (2000), Drobetz et al (2010) and El-Mashry et al (2010) on the other, argued that oil prices may be a contributor to stock returns given that oil is the major input for generating cargo service.…”
Section: Factor Constructionmentioning
confidence: 99%
“…However, research on the global shipping industry has lagged behind and was mainly concentrated on the investigation of the sources of shipping finance and capital structure of shipping companies, investment and valuation, corporate governance and risk measurement and management (Alexandridis et al, 2018). Grammenos and Marcoulis (1996), Poulakidas and Joutz (2009), Grammenos and Arkoulis (2002), Drobetz et al (2010Drobetz et al ( , 2016, El-Mashry et al (2010) and Westgaard et al (2017) found that factors such as inflation, industrial production, exchange rates, interest rates and oil prices were important for stock returns of global shipping companies. Kavussanos et al (2002aKavussanos et al ( , 2002b) investigated 38 international industries and found that various macroeconomic, global risk factors have had different impacts on industries as determined by their unique characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…Poulakidas and Joutz [9] showed that tanker demand comes from the oil demand, and thus tanker rates respond highly to the oil prices. El-Masry et al [10] explored the influence of macroeconomic factors, including oil prices on shipping firms' stock returns. They found that the increase in oil prices significantly influences the minority of shipping companies.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The low importance of country-specific factors in the stock performance of shipping companies is even more evident when foreign exchange rates are considered. Given that US dollars are the predominant currency that it is used by shipping companies, the majority actively uses currency hedging techniques that ultimately leave companies indifferent from fluctuations in the currency markets (El-Masry et al 2010).…”
Section: Literature Reviewmentioning
confidence: 99%